The Africans A Triple Heritage \ - 9 (Boston Little, Brown, 1986)
Companion volume to the PBS series. Provides an examination of modern Africa and the three major influences which have shaped it: indigenous traditions, Western culture, and Islamic culture.
Keywords: Africa -- civilization